Robust Portfolio Optimisation with Multiple Experts - Lutgens, Frank; Schotman, Peter C. (Review of Finance, 2010)
Abstract We consider mean-variance portfolio choice of a robust investor. The investor receives advice from J experts, each with a different prior for expected returns and risk, and follows a min-max portfolio strategy. The robust investor endogenously combines the experts' estimates. When experts agree on the main return generating factors, the investor relies on the advice of the expert with the strongest prior. Dispersed advice leads to averaging of the alternative estimates. The robust investor is likely to outperform alternative strategies. The theoretical analysis is supported by numerical simulations for the 25 Fama-French portfolios and for 81 European country and value portfolios.